Gambaran Persepsi Citra Tubuh, Pengetahuan Gizi Seimbang, dan Perilaku Makan Remaja Putri di SMA Muhammadiyah 1 Pekanbaru - Annisa Dian Purwanti; Yessi Marlina (LPPM Hang Tuah Pekanbaru, 2022)
An adolescent girl is a group that is vulnerable to nutritional problems. Nutritional problems can be caused by negative body image perception, bad knowledge of balanced nutrition, and bad eating habits. This study aims to describe body image perception, knowledge of balanced nutrition, and eating habits among adolescent girls in Muhammadiyah 1 Pekanbaru High School. This study used the descriptive research method. The Population of this study is 210 adolescent girls aged 15-18 years old. Samples were taken from as many as 70 adolescent girls using simple random sampling. All data were collected using the BSQ-16 questionnaire, knowledge of balanced nutrition questionnaire, and Adolescent Food Habit Checklist (AFHC) questionnaire. All the data were analyzed univariately. The results showed that 55,9% of adolescent girls had a positive body image perception and 47,1% had negative body image perception, 88,6% had good knowledge of balanced nutrition and 11,4% had sufficient knowledge of balanced nutrition, and 45,7% had a good eating habit and 54,3% had a bad eating habit. It is recommended to make counseling and health promotion to prevent bad eating habits and negative body image perception at school. Adolescent girls can improve their knowledge and eating habits in accordance with balanced nutrition guidelines and increase the perception of positive body image by focusing on their strengths and exploring their interests and talents.